2023
DOI: 10.1177/0145482x231167150
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Social Skills to Children and Adolescents With Visual Impairments: A Systematic Review

Abstract: Introduction: Social skills are acquired primarily through imitation using the visual system. As a result, people with visual impairments may experience difficulties in this area at any age, which can have a major effect on their social participation and on their quality of life. The objective of this study was to systematically review the effects of targeted interventions on social skills in children and adolescents with visual impairments. Methods: A systematic literature search was performed using databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(77 reference statements)
2
2
0
Order By: Relevance
“…These challenges encompass various aspects, such as barriers to enrolment in fashion schools, negative perceptions about the abilities of visually impaired individuals in fashion, lack of specialised sewing machines, and limited prior experiences with fashion design. This finding is consistent with previous studies conducted by Qaiser, Khan, and Tariq (2021) and Caron et al (2023), which identified challenges in design thinking and skills acquisition among visually impaired individuals. Qaiser et al, (2021) highlighted obstacles to web accessibility, while Caron et al (2023) emphasised challenges in skills acquisition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These challenges encompass various aspects, such as barriers to enrolment in fashion schools, negative perceptions about the abilities of visually impaired individuals in fashion, lack of specialised sewing machines, and limited prior experiences with fashion design. This finding is consistent with previous studies conducted by Qaiser, Khan, and Tariq (2021) and Caron et al (2023), which identified challenges in design thinking and skills acquisition among visually impaired individuals. Qaiser et al, (2021) highlighted obstacles to web accessibility, while Caron et al (2023) emphasised challenges in skills acquisition.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies conducted by Qaiser, Khan, and Tariq (2021) and Caron et al (2023), which identified challenges in design thinking and skills acquisition among visually impaired individuals. Qaiser et al, (2021) highlighted obstacles to web accessibility, while Caron et al (2023) emphasised challenges in skills acquisition.…”
Section: Discussionsupporting
confidence: 93%
“…They are related to higher self-esteem, better interpersonal relationships, lower incidence of problem behaviors, and better academic performance [33,34]. These skills are essential for successful adaptation in social situations and may include a variety of behaviors, such as cooperation, assertiveness, empathy, and communication skills, as well as catering to the diversity of the student body [35,36]. It has been observed that students with adequate social skills tend to experience lower levels of anxiety compared to their peers with less developed social skills [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent JVIB article entitled, "Teaching social skills to children and adolescents with visual impairments: A systematic review," Caron and colleagues presented a review of 32 studies of social skills instruction for children who are blind or have low vision, conducted across eight countries between 1983 and 2020 (Caron et al, 2023). I came to this review article in a unique position, as both the director of research at the American Foundation for the Blind (AFB) and as a woman who has been totally blind since birth and grew up receiving itinerant instruction during the 1990s.…”
mentioning
confidence: 99%